Particle verbs on the margins of Spanish lexicography and grammaticography - Wiesinger, Evelyn (Boletín de Filología, 2023)
This paper deals with so-called ‘particle verbs’ or ‘phrasal verbs’ in Peninsular Spanish lexicography and grammaticography from the 15th century to the present. These structures, situated halfway between the lexicon and the grammar, are considered marginal in modern Spanish from a typological and pan-Romance perspective. They also do not appear systematically in current dictionaries and grammars, where some are explicitly criticised. However, recent studies document certain (semi)productive patterns, some dating back to Old Spanish, that decline in diachronic corpus data starting in the 1500s (cf. Wiesinger 2020; in press a). The present contribution explores the interplay between this diachronic development and the treatment of particle verbs in normative and/or didactic Spanish dictionaries and grammars. In fact, the decline of Spanish particle verbs can be linked to normative and (re)latinising tendencies in Renaissance dictionaries and grammars, where certain adverbial particles are omitted and most particle verbs lack their own entries despite being used in the definitions. Although particle verbs are increasingly recognized in the works of the Real Academia Española in the 1700s and part of the 1800s, this traditional tendency reemerges in the 20th century and is slow to disappear.